Structural Optimization of Wind Turbine Tower Assemblies (Strojniški vestnik – Journal of Mechanical Engineering, 2017)
This paper presents a structural optimization approach for wind turbine tower assemblies. Finite element simulations were conducted to evaluate stress distribution and vibration behavior. The optimized tower design improves structural stability and reduces material consumption.
Keywords: Wind turbines; Tower structures; Structural optimization; Renewable energy; Stability analysis